2018
DOI: 10.1016/j.mam.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Brain docosahexaenoic acid uptake and metabolism

Abstract: Docosahexaenoic acid (DHA) is the most abundant n-3 polyunsaturated fatty acid in the brain where it serves to regulate several important processes and, in addition, serves as a precursor to bioactive mediators. Given that the capacity of the brain to synthesize DHA locally is appreciably low, the uptake of DHA from circulating lipid pools is essential to maintaining homeostatic levels. Although, several plasma pools have been proposed to supply the brain with DHA, recent evidence suggests non-esterified-DHA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 335 publications
1
113
0
Order By: Relevance
“…Specific membrane‐associated fatty acid transporters are involved in the transport of fatty acids into tissues, such as fatty acid translocase/CD36, plasma membrane fatty acid binding proteins, and fatty acid transport proteins (Glatz et al, ). Phospholipase A2 hydrolyzes PtdCho‐DHA to form lysophosphatidylcholine (lysoPtdCho)‐DHA, which is transported in circulation either bound to albumin or associated within the PL membrane of lipoproteins (Lacombe et al, ). Major facilitator superfamily domain‐containing protein 2a (Mfsd2a) is a lysoPtdCho transporter present in the endothelium of the BBB microvessels that has an affinity for lysoPtdCho‐bound fatty acids with a high capacity to transport lysoPtdCho‐DHA followed by lysoPtdCho‐18:0 and lysoPtdCho‐16:0 (Nguyen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific membrane‐associated fatty acid transporters are involved in the transport of fatty acids into tissues, such as fatty acid translocase/CD36, plasma membrane fatty acid binding proteins, and fatty acid transport proteins (Glatz et al, ). Phospholipase A2 hydrolyzes PtdCho‐DHA to form lysophosphatidylcholine (lysoPtdCho)‐DHA, which is transported in circulation either bound to albumin or associated within the PL membrane of lipoproteins (Lacombe et al, ). Major facilitator superfamily domain‐containing protein 2a (Mfsd2a) is a lysoPtdCho transporter present in the endothelium of the BBB microvessels that has an affinity for lysoPtdCho‐bound fatty acids with a high capacity to transport lysoPtdCho‐DHA followed by lysoPtdCho‐18:0 and lysoPtdCho‐16:0 (Nguyen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…or associated within the PL membrane of lipoproteins (Lacombe et al, 2018). Major facilitator superfamily domain-containing protein 2a (Mfsd2a) is a lysoPtdCho transporter present in the endothelium of the BBB microvessels that has an affinity for lysoPtdCho-bound fatty acids with a high capacity to transport lysoPtdCho-DHA followed by lysoPtdCho-18:0 and lysoPtdCho-16:0 (Nguyen et al, 2014).…”
Section: Correlation Of Brain and Spinal Cord Dha Concentration To Thmentioning
confidence: 99%
“…Aging is associated with brain atrophy and a loss of total tissue and fatty acid concentration per unit volume. As recently highlighted by Lacombe et al (29), it is important to consider brain fatty acid content as a percentage of total fatty acids and relative to the weight of total lipids when interpreting the meaning of altered status. Here, we observed a lower percentage and concentration of cortex DHA in older female APOE4 mice compared with their APOE3 or male counterparts.…”
Section: Lower Cortical Dha Content In Old Female Apoe4 Micementioning
confidence: 99%
“…Here, we observed a lower percentage and concentration of cortex DHA in older female APOE4 mice compared with their APOE3 or male counterparts. Previous studies in rodents have demonstrated the impact of aging on brain DHA (29) and identified DHA transporters across the blood-brain barrier using transgenic animal models [for review (30)]. Vandal et al (31) described the impact of APOE4 genotype on DHA uptake.…”
Section: Lower Cortical Dha Content In Old Female Apoe4 Micementioning
confidence: 99%
“…(Cao et al 2009). Due to the brains poor capacity to convert DHA on its own, almost all DHA must first pass through the blood brain barrier (BBB) (Lacombe et al 2018). The BBB is highly selective and contains specialized tight junctions for increased protection (Lo Van et al 2016).Transport of DHA is mediated by the Major Facilitator Superfamily Domain containing 2a (Mfsd2a) which is found to be expressed exclusively in the endothelium of the BBB (Nguyen et al 2014).…”
Section: Biology Of Epa and Dhamentioning
confidence: 99%